La inquisición en el caribe hispano, 1570-1610 - Gargallo García, Oliva (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
It is well-known that the Inquisition is an issue that has aroused the interest of many scholars of the different scientific disciplines, reflected this in diverse investigations and publications. There are several reasons for the interest in the inquisitorial subject, among them a more objective and analytical history that fades the traditional image of the scary scenes, the torture in the foal or the executions at the stake just to name a few. We note that in this vast historiographical production the inquisitorial theme in the Caribbean area has focused its object of study on the primitive American inquisition or also known as the American pre-inquisition, focusing specifically on mentioning the inquisitorial ministry of the first Inquisitor General of the West Indies Alonso Manso and only occasionally mention is made that some bishop has used the investiture inquisitorial. From this information and driven by knowing the development and the importance that the Inquisition acquired in the Hispanic Caribbean - under the administration of the Tribunal of the Holy Office of New Spain - as an institution with which it was tried to impose the surveillance of the Spanish Catholic customs, to prevent any attempt to break up religious and political unity and to prevent Lutheran and Calvinist ideas from finding fertile ground for their dissemination in the spirit of the colonial population. It is here that the desire to expand the knowledge and the reasons for choosing and developing the present research convinced that its study will provide a more complete information, new approaches, different questions and more definitive conclusions about the Inquisition in the Hispanic Caribbean. The study focuses on the analysis of the inquisitorial institution in the Hispanic Caribbean, from 1570 to 1610. The Caribbean Inquisition as an instrument for monitoring dogma and practice of the Catholic religion, morality and Spanish Catholic customs and, As a form of social control against any dissidence that involved persecution and repression, was exercised through the commissioner appointed by the Inquisitor General of New Spain. The commissioner as competent authority exercised the representation of the Tribunal of the Holy Office and in it relapsed all responsibility for the inquisitorial exercise in the Caribbean Hispanic islands.

Es conocido que la Inquisición es un tema que ha despertado el interés de muchos estudiosos de las distintas disciplinas científicas, reflejado esto en investigaciones y publicaciones diversas. Varias son las razones que explican el interés por el tema inquisitorial, entre ellas, una historia más objetiva y analítica que desvanezca la imagen tradicional de las escenas pavorosas, del tormento en el potro o de las ejecuciones en la hoguera sólo por mencionar algunas. Observamos que en esa vasta producción historiográfica el tema inquisitorial en el área caribeña ha enfocado su objeto de estudio a la primitiva inquisición americana o también conocida como la pre-inquisición americana, centrándose específicamente en mencionar el ministerio inquisitorial del primer inquisidor general de las Indias Occidentales Alonso Manso y sólo ocasionalmente se hace mención que algún obispo haya usado la investidura inquisitorial. A partir de esa información e impulsados por conocer el desenvolvimiento y la trascendencia que adquirió la Inquisición en el Caribe Hispano -bajo la administración del Tribunal del Santo Oficio de la Nueva España- como una institución con la que se trató de imponer la vigilancia de las costumbres católicas españolas, de evitar que pudiera surgir en el ánimo de la población colonial cualquier intento de rompimiento de la unidad religiosa y política y de impedir que las ideas luteranas y calvinistas encontraran terreno fértil para su difusión. Es aquí donde está el deseo de ampliar el conocimiento y los motivos para elegir y desarrollar la presente investigación convencida de que su estudio proporcionará una más completa información, nuevos planteamientos, diferentes interrogantes y conclusiones más definitivas en torno a la Inquisición en el Caribe Hispano. El estudio se centra en el análisis de la institución inquisitorial en el Caribe Hispano, de 1570 a 1610. La Inquisición caribeña como instrumento de vigilancia del dogma y de la práctica de la religión católica, de la moral y de las costumbres católicas españolas y, como forma de control social contra cualquier disidencia que suponía la persecución y la represión, fue ejercida a través del comisario nombrado por el Inquisidor General de la Nueva España. El comisario como autoridad competente ejerció la representación del Tribunal del Santo Oficio y en él recayó toda la responsabilidad del ejercicio inquisitorial en las islas hispanas caribeñas.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2011-0005; Inquisición; Caribe; Hispano; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2088